Determination prevalence of cymothoid parasite fish families in Iwofe (Port Harcourt) Rivers state - Gloria Wonodi*, Ugbomeh A.P. and Gabriel U.U. (African Journal of Biological Sciences, 2019)
The aim of this study is to provide information on the morphology of the Cymothoid parasites of Haemulidae and Elopidae from Iwofe in Port Harcourt determine physico chemical parameter of study area. To determine the percentage prevalence of Cymothoid parasite of both fish families in the study area. To determine the species of the Cymothoid parasite in the study area. To compare the structure and morphology of the different life stages of the Cymothoids. A total of seventy six (76) fishes from Iwofe landing site were examined, forty six (46) fishes were infected with a prevalence of 68%, Pomadasys perotetei had (96.7%), Pomadasys jubelini had (57.1%), Clarias arius had (50%) and none was also isolated from Mugil curema. During the period of study no Elopidae was found in this station, samples were obtained only from Haemulidae. The fishermen said they do not always have that catch because of the kind of net they use in fishing the morphology of the Cymothoid parasites of Haemulidae and Elopidae and the sampling sites was Iwofe water side . The isolated parasite that was collected was Cymothoid parasites and they Cymothoid sodwana, Cymothoid pleibeia, Cymothoid spp1, Cymothoid spp2, Nerocila acuminata, Nerocila lomatia and Nerocila orbignyi. The physical chemical parameters of the water was analyzed and the result showed that there was a significant difference in salinity, Dissolved Oxygen (DO) and Electrical Conductivity (EC) across the sampling stations. Pomadasyidae had a higher prevalence of isopods than the other fish hosts and more than one type of parasite was found in the mouth while Elopidae had the parasite on their fins and body wall and none was recorded in the mouth. The cephalon, pereomeres, pleomeres, pleotelson, eyes and marsupium was different in the Cymothoids studied. The parasite also affected the condition of the fish.
Keywords: Cymothoid parasites, Physicochemical parameters, Fish families, Iwofe